Engaging with employees during the closure of a telecommunications company in South Africa - Govind, Neelan Mahesh (My University, 2018)
With the increased pressure on the South African economy, many businesses are going through uncertain times. One of the industries that is under the most pressure is the telecommunications industry. All businesses within this industry are in for very uncertain times. Nashua Mobile is one of the businesses that has been seriously affected and announced their closure in April 2014. This research report will look at the history of the South African telecommunications industry, to try to understand the rationale behind the decision to close down Nashua Mobile. It will also look at understanding the uncertainties that were faced by the Nashua Mobile employees, and how the company engaged with them during this very difficult period. Through interviews with a sample of the employees from various departments and levels of the business, we will discover how successful Nashua Mobile’s engagement activities were.
MBA Thesis
Keywords: Communication in management,Business failures,Telecommunication,Employees -- Attitudes.